Reconstructing Islamic Education Based On Human Rights: A Synthesis Of Prophetic Ethics And Multicultural Values In Addressing The Global Humanitarian Crisis - Tri Wahyudi Ramdhan; Radina Mahdiana Mujib Riyanto; Junaidi Junaidi; Benadjih O Abdo (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2026)
Abstrak Munculnya fenomena intoleransi, diskriminasi gender, dan kekerasan berkedok kedisiplinan menunjukkan adanya jurang lebar antara teks agama yang memuliakan manusia dengan praktik di lapangan. Riset ini bertujuan merekonstruksi paradigma pendidikan Islam agar lebih humanis dan inklusif melalui integrasi etika profetik dan nilai multikulturalisme. Menggunakan metode Systematic Literature Review (SLR) dengan protokol PRISMA, peneliti membedah 24 dokumen kunci periode 2015-2025. Temuan menunjukkan bahwa Islam memiliki konsep HAM orisinal berbasis prinsip Karama (pemuliaan manusia) yang bersifat teosentris. Namun, implementasinya terhambat oleh interpretasi tekstualis, formalisme kurikulum, dan budaya patriarki yang kuat. Penelitian ini menganalisis krisis identitas pendidikan Islam di Indonesia. Sebagai solusi, riset ini merumuskan model "Pendidikan Islam Humanis-Transformatif". Model ini menggunakan Maqasid al-Shari’ah untuk melindungi lima hak dasar manusia: agama, jiwa, akal, keturunan, dan harta. Pendekatan ini menuntut transformasi peran guru menjadi fasilitator dialog yang demokratis dan empatik. Melalui Tafsir Tarbawi Multikultural, pendidikan Islam diarahkan untuk membentuk imunitas intelektual terhadap radikalisme sekaligus empati sosial. Hasil riset ini menjadi peta jalan strategis untuk mewujudkan ekosistem sekolah sebagai inkubator perdamaian global yang menghargai keberagaman sebagai rahmat Ilahi.Kata Kunci: Pendidikan Islam, Hak Asasi Manusia, Karama, Etika Profetik, Multikulturalisme, Humanis-Transformatif. Abstract The emergence of phenomena such as intolerance, gender discrimination, and violence disguised as discipline reveals a wide gap between religious texts that honor humanity and the actual practices on the ground. This research aims to reconstruct the paradigm of Islamic education to be more humanistic and inclusive by integrating prophetic ethics and multicultural values. Utilizing the Systematic Literature Review (SLR) method with the PRISMA protocol, the researcher analyzed 24 key documents from the 2015-2025 period. Findings indicate that Islam possesses an original concept of human rights based on the theocentric principle of Karama (the honoring of humanity). However, its implementation is hindered by textualist interpretations, curriculum formalism, and strong patriarchal culture. This study analyzes the identity crisis of Islamic education in Indonesia. As a solution, this research formulates the 'Humanistic-Transformative Islamic Education' model. This model utilizes Maqasid al-Shari’ah to protect five fundamental human rights: religion, life, intellect, lineage, and property. This approach demands a transformation of the teacher's role into a democratic and empathetic facilitator of dialogue. Through Multicultural Tafsir Tarbawi (educational exegesis), Islamic education is directed toward building intellectual immunity against radicalism while fostering social empathy. The results of this research serve as a strategic roadmap to realize the school ecosystem as an incubator for global peace that values diversity as a divine blessing (rahmat Ilahi).Keywords: Islamic Education, Human Rights, Karama, Prophetic Ethics, Multiculturalism, Humanist-Transformative.